Effect of High-Intensity Interval Training (HIIT) on Increasing VO2max in Pemalang Futsal Athletes - Muhammad Ainu Ridho; Ranu Baskora Aji Putra (Universitas Negeri Semarang, 2026)
This study aims to analyze the effect of High Intensity Interval Training (HIIT) on increasing VO₂max capacity in futsal athletes at Corner Futsal Academy. The problem with the study is the low cardiorespiratory endurance in athletes, which causes fatigue at the end of the game and has an impact on decreased performance. This study uses an experimental method with a pretest-posttest design of one group. The sample size was 25 athletes, selected using the total sampling technique. VO₂max is measured using the Multistage Fitness Test. The HIIT training program is implemented for 8 weeks, twice a week (16 sessions). The data were analyzed using descriptive statistics, Shapiro-Wilk test, Wilcoxon test, and N-Gain test.The results showed an increase in the mean VO₂max from 40.81 ± 5.64 to 44.38 ± 5.74 mL/kg/min, which represented an increase of 3.57 mL/kg/min (8.7%). The Wilcoxon test showed a significant improvement (Z = -3.87; p < 0.001) with a large effect size (r = 0.77). However, an N-Gain value of 5.9% is categorized as ineffective. It is concluded that HIIT significantly affects VO₂max, but its practical effectiveness still needs to be optimized.